Hypoparathyroidism presenting as cognitive dysfunction. (23rd May 2013) - Kumar, Gunjan; Kaur, Darshpreet; Aggarwal, Puneet; Khurana, Tilak
Abstract : Metabolic dysfunction in hypoparathyroidism is an important cause of intracranial calcifications, which cause cognitive impairment depending on the calcified areas leading to difficulties in executing activities of daily living. We report a case of a 25-year-old man who presented with gradually decreasing organisational skills, memory problems and difficulty in carrying out daily activities. CT imaging of the brain showed extensive calcification in the basal ganglia and cerebral white matter. Comprehensive health-related quality of life and cognitive assessment revealed significant affliction in his activities of daily living along with impairment in recall memory, executive functions and verbal fluency. Owing to late diagnosis, chronicity of cognitive problems could not prevent him from discontinuing his college education.